Genomic data from Galápagos penguin ( Spheniscus mendiculus ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The Galápagos penguin is endemic to the Galápagos Islands, and is the only penguin with breeding colonies north of the equator. The cool waters of the Humboldt and Cromwell Currents allow the species to survive in the tropics, and they have evolved unique adaptations to survive in a tropical environment. The International Union for Conservation of Nature (IUCN) classifies them as endangered. We sequenced the genome of an adult Galápagos penguin from Galápagos Islands (provided by Patricia Parker) to a depth of approximately 87x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled scaffolds of high quality sequences total 1.35Gb, with the contig and scaffold N50 values of 70.85Kb and 0.36Mb respectively. We identified 16390 protein-coding genes. ...